(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the role of business education in promoting financial literacy among senior secondary school students. Using an exploratory research design, the study relied on qualitative data obtained through an extensive review of relevant literature. The study was anchored on the social learning theory which explains how students acquire financial skills not only through formal instruction but also by observing, imitating, and practicing financial behaviors The study reveal that business education significantly enhances students’ understanding of basic financial concepts such as savings, budgeting, investment, and credit management. It also shapes positive financial attitudes and strengthens decision-making skills, thereby preparing students for effective personal financial management. The study further highlights that business education bridges the gap between theoretical knowledge and practical application, equipping students with lifelong financial competencies necessary for self-reliance and national economic development. The study concludes that business education is not only an academic necessity but also a strategic tool for fostering financial responsibility and sustainable growth. Thus, the study recommended that teachers of business education should be regularly trained and retrained to update their knowledge of financial literacy concepts and modern teaching methods.